The Relationship Between Leg Length and Flexibility on Smash Ability in Sepaktakraw Game - Nawir, Nukhrawi; Amahoru, Nurul Musfira (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to find out the relationship between leg length and flexibility on smash ability in sepaktakraw games. This research is a type of correlational descriptive research. The population of this study is all students of SMA Negeri 22 Makassar with a research sample of 100 male students who are randomly selected. The data analysis techniques used are simple and multiple correlation analysis techniques. Based on the results of data analysis, it is concluded that: There is a significant relationship between leg length and smash ability in the sepaktakraw game, (ro = 0.564 > rt = 0.195); There was a significant relationship between the flexibility to smash ability in sepaktakraw game, (ro = 0.588 > rt = 0.195); There was a significant relationship between leg length and flexibility on smash ability in the game of sepaktakraw (Ro = 0.588 > Rt = 0.195).